FAK mediates LPS-induced inflammatory lung injury through interacting TAK1 and activating TAK1-NFκB pathway - Xi Chen; Ying Zhao; Xu Wang; Yimin Lin; Weixin Zhao; Di Wu; Jingye Pan; Wu Luo; Yi Wang; Guang Liang (2022)
Abstract Acute lung injury (ALI), characterized by inflammatory damage, is a major clinical challenge. Developing specific treatment options for ALI requires the identification of novel targetable signaling pathways. Recent studies reported that endotoxin lipopolysaccharide (LPS) induced a TLR4-dependent activation of focal adhesion kinase (FAK) in colorectal adenocarcinoma cells, suggesting that FAK may be involved in LPS-induced inflammatory responses. Here, we investigated the involvement and mechanism of FAK in mediating LPS-induced inflammation and ALI. We show that LPS phosphorylates FAK in macrophages. Either FAK inhibitor, site-directly mutation, or siRNA knockdown of FAK significantly suppresses LPS-induced inflammatory cytokine production in macrophages. FAK inhibition also blocked LPS-induced activation of MAPKs and NFκB. Mechanistically, we demonstrate that activated FAK directly interacts with transforming growth factor-β-activated kinase-1 (TAK1), an upstream kinase of MAPKs and NFκB, and then phosphorylates TAK1 at Ser412. In a mouse model of LPS-induced ALI, pharmacological inhibition of FAK suppressed FAK/TAK activation and inflammatory response in lung tissues. These activities resulted in the preservation of lung tissues in LPS-challenged mice and increased survival during LPS-induced septic shock. Collectively, our results illustrate a novel FAK-TAK1-NFκB signaling axis in LPS-induced inflammation and ALI, and support FAK as a potential target for the treatment of ALI.